Investigating Proprietary Software Ecosystem Governance and Health: An Updated and Refined Perspective - Costa, Luiz Alexandre; Fontão, Awdren; Santos, Rodrigo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
Although the approaches conceptualizing software ecosystems (SECO) have gained more relevance since 2010, there are not many studies addressing proprietary SECO. In a proprietary SECO, organizations are concerned with keeping their assets protected by intellectual property so that they are not exposed publicly, preventing this information from being used by competitors. Understanding how the governance mechanisms works and how organizations handle incidents on their platforms are real challenges in this scenario. In this work, we report three main goals: i) providing an update on SECO governance mechanisms and SECO health metrics; ii) analyzing SECO classifications and evaluating the evolution of proprietary SECO; and iii) exploring the organization's strategies and investigating SECO incident management process. To do so, a longitudinal literature study was performed on SECO covering 2006 to 2015. As such, we analyzed 422 studies from 2016 to 2020 and provided an updated perspective based on seven research questions, as well as a refined perspective on proprietary SECO and a deeper understanding about incident management process. Our findings reveal that governance strategies aimed to share knowledge provides continuous innovation and increases competitive advantage in the software market.